Human biomonitoring of PCDDs, PCDFs, and PCBs in women living in a Northern Italy industrial area - Dellatte, Elena; Abate, Vittorio; Abballe, Annalisa; De Filippis, Stefania Paola; De Luca, Silvia; Ferri, Fabiola; Fulgenzi, Anna Rita; Iacovella, Nicola; Iamiceli, Anna Laura; Ingelido, Anna Maria; Marra, Valentina; Miniero, Roberto; et al. (Environmental science and pollution research international, 2025)
In Brescia , a highly industrialized city in the Lombardy Region (Northern Italy) classified as a SIN (Contaminated Site of National Interest), a human biomonitoring study was carried out on breast milk of two groups of women residing in areas with presumably different levels of exposure to polychlorodibenzo- p -dioxins, polychlorodibenzofurans, and polychlorobiphenyls. This study was aimed at evaluating the possible difference between women living in Brescia and women living far from it but in the same Region. Between 2016 and 2018, 82 women were enrolled (41 “exposed” subjects and 41 “not exposed”), breast milk samples were collected, and a specific questionnaire was administered to the donors. Data obtained were processed by robust regression and Principal Component Factor Analysis. The differences in concentration between the two groups were significant for all the classes of analytes (except for PCDDs). The concentration increase rates from the not exposed to the exposed group resulted highly significant: some PCB congeners showed increase rates more than 1000 ng/g lb per one-unit change of the independent variable. Among the variables significantly associated with the observed concentrations, age showed the greatest influence, while BMI showed a counteracting effect. Consumption of vegetable oil and fruit resulted to possibly influence the chemicals body burden. For the not exposed group, the levels appear to be in line with the decreasing trend (2001–2018) observed for these contaminants in Italy.